The best time travel stories of the 20th century - Greenberg, Martin Harry; Turtledove, Harry (New York : Ballantine Books, 2005)
Presents eighteen stories about time travel by popular science fiction and fantasy authors, chosen by the editors as the best of the twentieth century, including selections from Ray Bradbury, Nancy Kress, Robert Silverberg, and others.
"Del Rey.".
Adult
Keywords: Science fiction, American; Science fiction, English; Short stories, American; Short stories, English; Time travel -- Fiction; Science fiction; Short stories; Time travel -- Fiction; Fantastic fiction, American; Fantastic fiction, English; Fantastic fiction